2021
DOI: 10.1007/s00421-021-04595-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolated finger flexor vs. exhaustive whole-body climbing tests? How to assess endurance in sport climbers?

Abstract: Purpose. Sport climbing requires high intensity finger flexor contractions, along with a substantial whole-body systemic oxygen uptake (V ̇O2) contribution. Although fatigue is often localised to the finger flexors, the role of systemic V ̇O2 and local aerobic mechanisms in climbing performance remains unclear. As such, the primary purpose of this study was to determine systemic and local muscle oxygen responses during both isolated finger flexion and incremental exhaustive whole-body climbing tests. The secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 39 publications
(77 reference statements)
7
42
1
Order By: Relevance
“…•kg −1 and lowered muscle oxygen saturation of the FDP by 7% (Baláš et al, 2021). In this study, TTE decreased with steeper wall angle and the association between TTE and wall angle followed a hyperbolic function (Figure 2) same to the power or speed and duration relationship (Jones et al, 2019).…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…•kg −1 and lowered muscle oxygen saturation of the FDP by 7% (Baláš et al, 2021). In this study, TTE decreased with steeper wall angle and the association between TTE and wall angle followed a hyperbolic function (Figure 2) same to the power or speed and duration relationship (Jones et al, 2019).…”
Section: Discussionsupporting
confidence: 54%
“… Noé et al (2001) reported that an increase of 10° (−10° from vertical) induced ∼47% increase in mean vertical force on handholds and, therefore, more intense finger flexor contractions. Furthermore, an increase of wall angle by 15° from vertical elevated heart rate by an average of ∼24 beats per min, oxygen uptake by ∼9 mL⋅min –1 ⋅kg –1 and lowered muscle oxygen saturation of the FDP by 7% ( Baláš et al, 2021 ). In this study, TTE decreased with steeper wall angle and the association between TTE and wall angle followed a hyperbolic function ( Figure 2 ) same to the power or speed and duration relationship ( Jones et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations